Розвиток повітряних ліній електропередачі з застосуванням волоконно-оптичних кабелів - Черкашина, Вероніка Вікторівна (Вінницький національний технічний університет, 2018)
Обґрунтовано доцільність застосування волоконно-оптичних кабелів при розвитку повітряних ліній електропередачі, що дозволить розширити функціональні можливості об’єкта за рахунок створення систем моніторингу параметрів ліній та автоматизованих систем диспетчерського керування.

The use of fiber optic cables in the development of air lines will expand the functionality of the object through the creation of automated dispatch control systems and systems monitoring parameters of the lines. But it follows that the procedure for choosing a fiber-optic cable for the construction of fiber-optic communication lines on the power lines cannot be standar-dized; therefore, the design organizations need to carry out additional research, taking into account the entire spectrum of technical and economic information on the construction and operation of air with expanded functionality. The exploitation of electric networks has shown that the direction of transmission of electric energy, especially in main sections, coincides with the directions of information transmission. These circumstances contribute to the feasibility of combining power transmission lines with communication lines in fiber optic communication lines over power lines. It has shown that the direction of transmission of electric energy, especially in main sections, coincides with the directions of information transmission. These circumstances contribute to the feasibility of combining power transmission lines with communication lines in fiber optic communication lines over power lines. During the design of fiber-optic communication lines over power lines it is necessary to take into account that, regardless of the technical solution of the dielectric optical self-supporting cable during the passage of the signal over the fiber optic cable, there is a decrease in the signal strength level, in addition, due to the dispersion the signal goes distorted at the receiving end. The expediency of using fiber-optic cables in the development of overhead power transmission lines is substantiated in the article, which will allow expanding the functionality of the facility due to the creation of dispatch control systems and monitoring of line parameters.
Development of Overhead Power Lines with the Use of Fiber-optic Cable
Keywords: електрична енергія; грозозахисний трос; фазне проведення; автоматизовані системи диспетчерського керування; лінії зв'язку; напруга; fiber-optic cable; fiber-optic communication lines; air line; lightning protection cable; phase conduct